2021
DOI: 10.1186/s12931-021-01828-3
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of leukocyte immunoglobulin-like receptor B4 on interstitial macrophages in COPD; their possible protective role against emphysema formation

Abstract: Background Leukocyte immunoglobulin-like receptor B4 (LILRB4) is one of the inhibitory receptors in various types of immune cells including macrophages. Previous reports suggested that LILRB4 could be involved in a negative feedback system to prevent excessive inflammatory responses. However, its role has been unclear in chronic obstructive pulmonary disease (COPD), in which macrophages play a crucial role in the pathogenesis. In this study, we aimed to examine the changes of LILRB4 on macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“… 29 , 30 LILRB4, leukocyte immunoglobulin-like receptor B4, is an inhibitory receptor on macrophages that prevents excessive inflammation. 31 LGALS3 (galectin-3) is a galactose-specific lectin that regulates macrophage adhesion and migration. Loss of LGALS3 results in increased expression of proinflammatory genes.…”
Section: Resultsmentioning
confidence: 99%
“… 29 , 30 LILRB4, leukocyte immunoglobulin-like receptor B4, is an inhibitory receptor on macrophages that prevents excessive inflammation. 31 LGALS3 (galectin-3) is a galactose-specific lectin that regulates macrophage adhesion and migration. Loss of LGALS3 results in increased expression of proinflammatory genes.…”
Section: Resultsmentioning
confidence: 99%
“…LILRB4 was found to be upregulated on interstitial macrophages in human chronic obstructive pulmonary disease and mouse emphysema models. Upregulation of LILRB4 may exert a protective effect against emphysema formation by decreasing the expression of matrix metalloproteinase MMP-12 in the lungs [125]. Moreover, in other inflammatory lung conditions, such as acute lung injury, a lack of LILRB4 expression would exacerbate acute lung injury through NF-κB signaling in bone marrow-derived macrophages [126].…”
Section: Studies On the Association Of Lilrb4 With Other Diseasesmentioning
confidence: 99%
“…Increased MMP‐12 production led to more severe emphysema lesions. However, up‐regulation of LILRB4 protected against chronic obstructive disease lung disease (Mitsune et al., 2021). Patel et al.…”
Section: Lilrb4mentioning
confidence: 99%
“…Increased MMP-12 production led to more severe emphysema lesions. However, up-regulation of LILRB4 protected against chronic obstructive disease lung disease (Mitsune et al, 2021). Patel et al (2021) found that six proteins (IL-NF-6, CKAP4, Gal-9, IL-1ra, LILRB4 and PD-L1) were associated with the severity of COVID-19 and were proportional to disease symptom severity.…”
Section: Lilrb4 and Inflammationmentioning
confidence: 99%